The Holocene environmental changes revealed from the sediments of the Yarkov sub-basin of Lake Chany, south-western Siberia - Krivonogov, S. K.; Zhdanova, A. N.; Solotchin, P. A.; Kazansky, A. Y.; Chegis, V. V.; Liu, Z.; Song, M.; Zhilich, S. V.; Rudaya, Natalia A.; Cao, X.; Palagushkina, O. V.; Nazarova, L. B.; et al. (Geoscience frontiers)
Lake Chany is the largest endorheic lake in Siberia whose catchment is entirely on the territory of Russia. Its geographical location on the climate-sensitive boundary of wet and dry landscapes provides an opportunity to gain more knowledge about environmental changes in the West Siberian interior during the Holocene and about the evolution of the lake itself. Sediment cores obtained from the Yarkov subbasin of the lake in 2008 have been comprehensively studied by a number of approaches including sedimentology and AMS dating, pollen, diatom and chironomid analyses (with statistical interpretation of the results), mineralogy of authigenic minerals and geochemistry of plant lipids (biomarker analysis.). Synthesis of new results presented here and published data provides a good justification for our hypothesis that Lake Chany is very young, no older than 3.6 ka BP. Before that, between 9 and 3.6 ka BP, the Chany basin was a swampy landscape with a very low sedimentation rate; it could not be identified as a water body. In the early lake phase, between 3.6 and 1.5 ka BP, the lake was shallow, 1.2-3.5 m in depth, and it rose to its modern size, up to 6.5 m in depth, during the last millennium. Our data reveal important changes in the understanding of the history of this large endorheic lake, as before it was envisioned as a large lake with significant changes in water level since ca. 14 ka BP. In addition to hydrology, our proxies provide updates and details of the regional vegetation and climate change since ca. 4 ka BP in the WestSiberian forest-steppe and steppe. As evolution of the Chany basin is dependent on hydroclimatic changes in a large region of southern West Siberia, we compare lake-level change and climate-change proxies from the other recently and most comprehensively studied lakes of the region.